Zinc finger protein transcription factors: Integrated line of action for plant antimicrobial activity. (July 2019) - Noman, Ali; Aqeel, Muhammad; Khalid, Noreen; Islam, Waqar; Sanaullah, Tayyaba; Anwar, Muhammad; Khan, Shahbaz; Ye, Wenfeng; Lou, Yonggen
Abstract: The plants resist/tolerate unfavorable conditions in their natural habitats by using different but aligned and integrated defense mechanisms. Such defense responses include not only morphological and physiological adaptations but also the genomic and transcriptomic reconfiguration. Microbial attack on plants activates multiple pro-survival pathways such as transcriptional reprogramming, hypersensitive response (HR), antioxidant defense system and metabolic remodeling. Up-regulation of these processes during biotic stress conditions directly relates with plant survival. Over the years, hundreds of plant transcription factors (TFs) belonging to diverse families have been identified. Zinc finger protein (ZFP) TFs have crucial role in phytohormone response, plant growth and development, stress tolerance, transcriptional regulation, RNA binding and protein-protein interactions. Recent research progress has revealed regulatory and biological functions of ZFPs in incrementing plant resistance to pathogens. Integration of transcriptional activity with metabolic modulations has miniaturized plant innate immunity. However, the precise roles of different zinc finger TFs in plant immunity to pathogens have not been thoroughly analyzed. This review consolidates the pivotal functioning of zinc finger TFs and proposes the integrative understanding as foundation for the plant growth and development including the stress responses. Highlights: ZFPs have crucial roles in plant life cycle. ZFPs can be induced upon plant pathogen interactions. Growth and stress related signaling pathways embed overlapping and crosstalk mechanism among each other. Constitutive expression of different ZFP TFs may vary among organs of same plant. Differential expression of ZFPs highlights interface of signaling pathways as network to regulate stress tolerance.